ANALISIS PERATURAN LEMBAGA OTORITAS JASA KEUANGAN NO. 37/POJK/2018 MENGENAI TRANSAKSI JASA KEUANGAN BERBASIS TEKNOLOGI INFORMASI (CROWDFUNDING) - Elfrida Ratnawati Gultom; Muhammad Rakadhitia Hilmi Aqiilah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Technology-based fundraising, also known as crowdfunding, has emerged as a new trend in corporate funding needs. Crowdfunding is growing rapidly because of technological developments, especially the development of the internet. Today, most people are connected to the Internet. Hence, it has become an area that is in great demand by the masses. In writing this book, the prescriptive research method was used to examine and examine library materials. In this study, researchers used library materials as data to be analyzed. The survey targets are laws and government policies related to crowdfunding, as well as academic journals which are also included as secondary data. This paper examines the forms of legal protection for parties and the problems faced by financial service institutions in providing legal protection efforts to parties in crowdfunding services, and how the current crowdfunding mechanism is. This is intended to clarify whether the results of this paper explain how legal protection works in technology-assisted financing services transactions in Indonesia.